2007
DOI: 10.1016/j.cattod.2007.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Promotion effect of residual K on the decomposition of N2O over cobalt–cerium mixed oxide catalyst

Abstract: A series of cobalt-cerium mixed oxide catalysts (Co 3 O 4 -CeO 2 ) with a Ce/Co molar ratio of 0.05 were prepared by co-precipitation (with K 2 CO 3 and KOH as the respective precipitant), impregnation, citrate, and direct evaporation methods and then tested for the catalytic decomposition of N 2 O. XRD, BET, XPS, O 2 -TPD and H 2 -TPR methods were used to characterize the catalysts. Catalysts with a trace amount of residual K exhibited higher catalytic activities than those without. The presence of appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 31 publications
3
42
0
1
Order By: Relevance
“…Ohnishi et al [19] have recently reported the role of alkali and alkaline earth metals doping in enhancing the N 2 O decomposition activity of Co 3 O 4 spinel oxide catalyst. Concurrent with this study, the positive influence of alkaline metals during N 2 O decomposition was also reported for other catalytic systems like Co 3 O 4 -CeO 2 [13], Co-Al [29], CuO [38], NiO [39], and Rh/Al 2 O 3 [10,11] catalysts. In the pervious references, it was argued that the alkali metal content plays a vital importance in enhancing the N 2 O decomposition activity.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Ohnishi et al [19] have recently reported the role of alkali and alkaline earth metals doping in enhancing the N 2 O decomposition activity of Co 3 O 4 spinel oxide catalyst. Concurrent with this study, the positive influence of alkaline metals during N 2 O decomposition was also reported for other catalytic systems like Co 3 O 4 -CeO 2 [13], Co-Al [29], CuO [38], NiO [39], and Rh/Al 2 O 3 [10,11] catalysts. In the pervious references, it was argued that the alkali metal content plays a vital importance in enhancing the N 2 O decomposition activity.…”
Section: Introductionsupporting
confidence: 62%
“…nitrogen and oxygen. Wide variety of catalysts were tested such as metal surfaces [8], supported metals [9][10][11], metal oxides [12,13], supported oxides [14,15], ternary oxides [16], spinels [13,[17][18][19][20][21][22][23][24][25], perovskites [26] hydrotalcites [27][28][29], and zeolites [30][31][32][33][34][35][36][37]. Focusing our attention to spinel oxide catalysts, a high laugh gas decomposition activity was reported for cobalt containing spinel oxides, such as Co 3 O 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Nitrates of cobalt, cerium and alkali, or alkaline earth metals were used in appropriate quantities. The details of the method can be seen in the Supporting Information or in our previous paper (15). The catalyst is referred to as CC-M-x (M indicates the doping alkali or alkaline earth metal; x indicates the molar ratio of M/Co, so that x ) 0 for the undoped catalyst).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the promotion effect of K was found to be more significant than ceria (15,16). Here, the influence of alkali metal additives on the chemistry environments of Co ions may be an important reason for their high activities.…”
Section: Catalytic Activity Measurementsmentioning
confidence: 99%
“…It was found that the catalysts with a high efficiency during the low-temperature N2O reduction reaction contained rhodium supported on zirconia, praseodymiumdoped ceria or mixed systems incorporating titanium oxide and cerium oxide, additionally coated with rhodium [17][18][19]. However, research into the cobalt-based catalysts and promoted alkali metals: sodium and potassium shows that it is possible to achieve complete conversion at a temperature below 450°C [20,21]. Such catalysts are very active in this reaction and do not contain precious metals, which consequently further reduces their cost [22].…”
Section: Introductionmentioning
confidence: 99%